Predictive Factors of the Entrepreneurial Performance of Undergraduates - Shaowei, Qu; Tianhua, Li; Miao, Zhang (Frontiers in Psychology, 2022)
College students have gradually become the main force of entrepreneurship in mass entrepreneurship and innovation. However, their entrepreneurial performance was not as good as expected. We have done research to analyze the predictive factors of entrepreneurial performance of college students and put forward targeted suggestions, hoping to be helpful to improve the entrepreneurial performance of them. Based on questionnaire data obtained from 2097 college student entrepreneurs, this study uses structural equation model to analyze the predictive factors of the entrepreneurial performance of college students. The survey results of the questionnaire show that both personal and behavioral factors influence the entrepreneurial performance of college students. In this study, personal factors in this study mainly include entrepreneurial willingness, personality and ability of entrepreneurs. Behavioral factors mainly refer to the positive behaviors of entrepreneurs that can affect entrepreneurial performance.